Suitability of Cocopeat as a Transplanting Media in the Polytube of Magnolia elegans (Blume.) H. Keng Seedlings - Irawan, Arif Irawan; Hidayah, Hanif Nurul Hidayah (Jurnal Wasian, 2014)
This study aims to determine the suitability of using cocopeat as planting media at transplanting containers in the polytube of the cempaka seedlings growth. The method used in this research was implementing a trial use of cocopeat as transplanting media in the polytube and being compared to the growth of cempaka seedlings in polytubes and polybags containing topsoil. The parameters observed included percent survival (%), height (cm), and diameter (cm) of the plants. Through the t-test it was shown that the parameters of diameter, height, and percent survival of the cempaka seedlings using cocopeat as a transplanting media were significantly different than those using top soil as a transplanting media.